Repercusiones de las carreteras orbitales de la Comunidad de Madrid en los cambios de usos del suelo - Serrano Cambronero, Milagros; Antón Burgos, F. Javier; Gago García, Cándida (Anales de Geografía de la Universidad Complutense, 2004)
This paper introduces the different changes of the ground in the city of Madrid producing by the construction of new orbital motorways: M-40, M-45 and M-50; this construction is producing new types of land’s uses, increasing sprawl of the city, land’s uses conflicts, and transformation of rural uses of ground to urban ones. The research has been done using remote sensing and Geographic Information Systems.